Chryseobacterium indologenes in four patients with leukemia. Issue 4 (23rd June 2015) - Deng, L.; Li, M.F.; Li, Y.H.; Yang, J.L.; Zhou, X.
Abstract Chryseobacterium indologenes is a rare opportunistic pathogen causing hospital‐acquired infection. We present 4 patients with leukemia associated with C. indologenes infection. Two of the patients, undergoing peripheral blood allogeneic hematopoietic stem cell transplantation (alloHSCT) from human leukocyte antigen‐identical sibling donors, died of pneumonia caused by C. indologenes with or without Pseudomonas aeruginosa. Blood infection with C. indologenes was found in the other 2 patients during chemotherapy, 1 of which was a central venous catheter‐related bloodstream infection. Both patients were cured with or without the sensitive antibiotic. Three of these 4 isolates were susceptible to trimethoprim‐sulfamethoxazole only in vitro. Although C. indologenes has a weak toxicity, it can be lethal for the super‐immunocompromised patients, such as those treated with alloHSCT.